133k views
4 votes
HELLPPP

Solve the system by substitution.
-9x-10y=12
−3x+3=y

2 Answers

4 votes
HELLPPP

Solve the system by substitution.
-9x-10y=12
−3x+3=y


X=2
Y= -3
User Prasad Kp
by
5.2k points
1 vote

Answer:


x=2\\y=-3

Explanation:

We have:


-9x-10y=12\\-3x+3=y

Since we already have a variable value (
y) in the second equation, it would be easiest to substitute the value for
y in the first equation:


-9x-10(-3x+3)=12

Distribute
-10 into
(-3x+3):


-9x+30x-30=12

Combine like terms:


21x-30=12

Add
30 to both sides of the equation:


21x=42

Divide by the coefficient of
x, which is
21:


x=2

_

Now that we have our
x value, we can substitute that in to the second equation to find our
y value:


-3(2)+3=y

Multiply:


-6+3=y

Combine like terms:


-3=y

User Donut
by
5.4k points